Activation of NLRP3 Inflammasome by Advanced Glycation End Products Promotes Pancreatic Islet Damage. (5th November 2017) - Kong, Xiang; Lu, Ai-Ling; Yao, Xin-Ming; Hua, Qiang; Li, Xiao-Yong; Qin, Li; Zhang, Hong-Mei; Meng, Guang-Xun; Su, Qing
Abstract : Accumulation of advanced glycation end products (AGEs) contributes to ageing and age-related diseases, especially type 2 diabetes. The NLRP3 inflammasome, as a vital component of the innate immune system, is implicated in the pathogenesis of type 2 diabetes. However, the role of the NLRP3 inflammasome in AGE-induced pancreatic islet damage remains largely unclear. Results showed that administration of AGEs (120 mg/kg for 6 weeks) in C57BL/6J mice induced an abnormal response to glucose (as measured by glucose tolerance and insulin release), pancreatic β -cell ultrastructural lesion, and cell death. These effects were associated with an excessive superoxide anion level, significant increased protein expression levels for NADPH oxidase 2 (NOX2), thioredoxin-interacting protein (TXNIP), NLRP3, and cleaved IL-1 β, enhanced caspase-1 activity, and a significant increase in the levels of TXNIP–NLRP3 protein interaction. Ablation of the NLRP3 inflammasome or treatment with antioxidant N -acetyl-cysteine (NAC) clearly ameliorated these effects. In conclusion, our results reveal a possible mechanism for AGE-induced pancreatic islet damage upon NLRP3 inflammasome activation.